2007
DOI: 10.1089/jwh.2007.0437
|View full text |Cite
|
Sign up to set email alerts
|

Progression to AIDS and Death and Response to HAART in Men and Women from a Multicenter Hospital-Based Cohort

Abstract: We have found no differences in HIV progression and response to HAART attributable to gender among patients accessing the Spanish hospital network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
0
12
1
2
Order By: Relevance
“…The observed differences in mortality on ART were interpreted as background differences in mortality between men and women unrelated to the HIV epidemic . In contrast, studies from high‐income countries with sufficient access to health care have shown that sex has no major impact on disease progression or mortality . In our study, mortality was still higher in men after adjusting for socio‐economic factors and baseline CD4 cell count, suggesting that advanced disease at enrolment alone could not explain the excess mortality in men.…”
Section: Discussioncontrasting
confidence: 73%
“…The observed differences in mortality on ART were interpreted as background differences in mortality between men and women unrelated to the HIV epidemic . In contrast, studies from high‐income countries with sufficient access to health care have shown that sex has no major impact on disease progression or mortality . In our study, mortality was still higher in men after adjusting for socio‐economic factors and baseline CD4 cell count, suggesting that advanced disease at enrolment alone could not explain the excess mortality in men.…”
Section: Discussioncontrasting
confidence: 73%
“…Inadequate care for knowledge about HIV/AIDS among the lower educational level groups may delay an AIDS diagnosis until symptoms appeared [45]. Reports of disparities in HIV survival related to sex have been mixed, with some studies reporting higher survival among female individuals [36], [46], some reporting it among male individuals [47], or no difference [38], [48], [49]. Consistent with a previous study [50], IDUs presented less likely to progress to AIDS following HIV diagnosis compared with MSMs, which might be related to the younger age of IDUs compared with that of MSMs.…”
Section: Discussionmentioning
confidence: 99%
“…Increased age and decreased educational level have been previously associated with increased mortality [2224]. Reports of gender differences in HIV mortality have been mixed, with studies reporting higher male mortality [23], female mortality [25], or no difference [22, 26, 27]. Why single people are at higher risk and divorced or widowed people at lower risk of mortality compared to married people or people living together is not clear and may be related to the small numbers in each category.…”
Section: Discussionmentioning
confidence: 99%